KEPENTINGAN RUSIA DALAM MEMBERIKAN SUAKA POLITIK KEPADA EDWARD JOSEPH SNOWDEN - Ibrahim "; Irwan Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This research to explain interest of Russia with Snowden. Edward Joseph Snowden is a former Central Intelligence Agency (CIA) employee and a former contractor for National Security Agency (NSA) who leaked classified information to The Guardian and The Washington Post. Snowden who leaked classified information have Surveillance program doing by United State of America. The Surveillance Program is a cooperate between 9 big companies from United States, which: Yahoo!, Facebook, Google, Apple, Skype, Microsoft, PalTalk, YouTube, and AOL. After leaked classified information, U.S put a label to Snowden as traitor and spy. And today, Snowden lives in Russia and granted asylum and protection from RussiaThis research uses qualitative research method. Data obtained from books, journals, articles, dictionaries and websites. The concept used in this research is the role concept and using the theory of international organization.This research shows the interest of Russia in dealing and granted asylum request from Snowden. Russia given permission to Snowden for live in Russia and he already lives for 4 years. United State of America ask Russia to extradite Snowden back, but Russia reject that proposal.Keywords: Snowden, Extradition, and Surveillance Program